Nobiletin restores HFD-induced enteric nerve injury by regulating enteric glial activation and the GDNF/AKT/FOXO3a/P21 pathway - Yueshan Pang; Li Zhang; Zhuoting Zhong; Ni Yang; Yali Zheng; Weijun Ding (BMC, 2024)
Abstract Background To explore whether nobiletin has a protective effect on high-fat diet (HFD)-induced enteric nerve injury and its underlying mechanism. Methods An obesity model was induced by a HFD. Nobiletin (100 mg/kg and 200 mg/kg) and vehicle were administered by gastric gavage for 4 weeks. Lee's index, body weight, OGTT and intestinal propulsion assays were performed before sacrifice. After sampling, lipids were detected using Bodipy 493/503; lipid peroxidation was detected using MDA and SOD kits and the expression of PGP 9.5, Trem2, GFAP, β-tubulin 3, Bax, Bcl2, Nestin, P75 NTR, SOX10 and EDU was detected using immunofluorescence. The GDNF, p-AKT, AKT, p-FOXO3a, FOXO3a and P21 proteins were detected using western blotting. The relative mRNA expression levels of NOS2 were detected via qPCR. Primary enteric neural stem cells (ENSCs) were cultured. After ENSCs were treated with palmitic acid (PA) and nobiletin, CCK-8 and caspase-3/7 activity assays were performed to evaluate proliferation and apoptosis. Results HFD consumption caused colon lipid accumulation and peroxidation, induced enteric nerve damage and caused intestinal motor dysfunction. However, nobiletin reduced lipid accumulation and peroxidation in the colon; promoted Trem2, β-tubulin 3, Nestin, P75NTR, SOX10 and Bcl2 expression; inhibited Bax and GFAP expression; reduced NOS2 mRNA transcription; and regulated the GDNF/AKT/FOXO3a/P21 pathway. Nobiletin also promoted PA-induced impairment of ENSCs. Conclusions Nobiletin restored HFD-induced enteric nerve injury, which may be associated with inhibiting enteric nerve apoptosis, promoting enteric nerve survival and regulating the GDNF/AKT/FOXO3a/P21 pathway.